Análise comparativa dos regimes de capitalização simples e composta na matemática financeira - COSTA, João Wilham Pinheiro (2023)
In this text, the simple and compound capitalization regimes were explored, including definitions, calculation formulas, and examples of application. Additionally, a comparative analysis was carried out between the regimes, considering their advantages and disadvantages in different financial contexts, such as fixed and variable income investments, personal loans, and real estate financing. It was concluded that the choice between one regime or another should take into account factors such as term, interest rate, and the objective of the financial operation. Finally, limitations of the study were pointed out, and possible perspectives for future research, including the investigation of the tax implications of capitalization regimes and their effects on net investment income or debt cost.